2016
DOI: 10.1111/dmcn.13065
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of web‐based training to increase activity in children with cerebral palsy

Abstract: AIM To determine the efficacy of web-based training on activity capacity and performance in children with unilateral cerebral palsy (CP).METHOD In a matched-pairs randomized waitlist controlled trial, independently ambulant children and adolescents with unilateral CP were allocated to receive 30 minutes of training (intervention) 6 days per week, or usual care (waitlist control) for 20 weeks. Activity capacity was assessed using maximal repetitions of functional strength tasks and 6-minute walk test (6MWT); pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
123
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(126 citation statements)
references
References 23 publications
(51 reference statements)
1
123
1
1
Order By: Relevance
“…14 These results are consistent with a few other studies that have begun to identify a discrepancy between changes observed in the rehabilitation clinic (i.e. capacity) and a failure to increase UL performance in daily life both for adults 26,49 and children 50 (but see 51 ). When changes seen in the clinic do not carry over to life at home, then it is time to reconsider what is being delivered in the clinic and how it might need to be changed.…”
Section: Discussionsupporting
confidence: 89%
“…14 These results are consistent with a few other studies that have begun to identify a discrepancy between changes observed in the rehabilitation clinic (i.e. capacity) and a failure to increase UL performance in daily life both for adults 26,49 and children 50 (but see 51 ). When changes seen in the clinic do not carry over to life at home, then it is time to reconsider what is being delivered in the clinic and how it might need to be changed.…”
Section: Discussionsupporting
confidence: 89%
“…Our hypotheses were not supported in that there were no significant differences at 20 weeks in EF capacity or performance for children who were allocated to the Mitii TM group as compared to children in the waitlist control group. This is in contrast to primary outcomes of the larger RCT, in which significant improvements in upper limb function, visual perception, and physical strength were found at 20 weeks following the Mitii TM intervention [25,26] .…”
Section: Discussioncontrasting
confidence: 88%
“…This paper reports the EF results from an RCT of Mitii TM . The effectiveness of Mitii on improving motor planning and physical activity outcomes in this cohort has been reported [25,26] . The primary hypothesis for the present study was that Mitii™ would improve capacity on tests of EF.…”
mentioning
confidence: 81%
“…Protocol papers and additional outcomes papers were then sought for included articles where available. Nine studies, comprising 10 articles, two protocol papers, and one additional outcome paper, were included. Seven studies were RCTs, one was a case–control design, and the remaining an interrupted time‐series design .…”
Section: Resultsmentioning
confidence: 99%